The use of German intelligence and sabotage agents on the eve and during Nazi punitive operations period on occupied territory of Belarus in 1942–1944 - S. V. Kulinok (Омский научный вестник: Серия "Общество. История. Современность")
In the study based on unpublished sources, for the first time in Russian-language historiography, the process of sending German agents to collect intelligence and commit acts of sabotage during Nazi punitive operations against partisans and civilians in 1942–1944 is considered on the occupied territory of the BSSR. The purpose of the work is to investigate the mechanism of sending and the effectiveness of the work of German agents in partisan formations, which has not received due reflection in the studies. The methodological basis of the study is formed by the principle of consistency, value and anthropological approaches. The author comes to the conclusion that the Nazis carefully thought out the approach of using reconnaissance and sabotage agents, in connection with which, in the combat activities of partisan formations, counterintelligence work is a particular